Understanding disruptive behaviour in the juvenile prison estate. Issue 2 (8th May 2017) - Whiteside, Emma; Bond, Carol A.
Abstract : Purpose: Serious incidents of violent disruption within the national young-persons' prison estate endanger offenders, staff and visitors and have a significant impact. The purpose of this paper is to explore the function of and factors influencing violent disruptive behaviour. Design/methodology/approach: In total, 21 young people ( n =21) with a history of violence in custody were administered semi-structured interviews to explore the reasons for their behaviour. The data were explored using thematic analysis. Findings: Six themes were identified: attitude and propensity for violence, perceptions and intolerance of others, consequences of violent behaviour, the physical environment, previous indicators, and protective factors. Research limitations/implications: The study is reliant on self-report and thus may reflect biases. The presence of a recording device may have had an impact on responses. Logistical practicalities meant participants were approached via an intermediary which may have impacted on a willingness to participate. Practical implications: Several practical implications are identified: cognitive skills programmes which encourage consequential thinking, perspective-taking, communication skills and exploring alternative problem-solving strategies are of value. Shouting through doors and windows is a major source of provocation and should be addressed. The induction process provides opportunities for equality-awareness work. Gang membership issues are a major cause of violence, and attitudes around this should be addressed. Building trust between staff and young people helps reduce problems. Systems to provide access to facilities and to provide support to cope with stress and isolation may be of value. Originality/value: This study uses a qualitative approach to exploring young people's views on prison violence. The findings reflect previous research but strengthen the perspective that violence in prison serves several purposes for those involved and that violence-reduction strategies must be multi-modal to be effective.